Mathematical modeling of service life of cables polymer insulation - D. A. Polyakov; M. A. Kholmov; D. I. Plotnikov; K. I. Nikitin; U. V. Polyakova (Омский научный вестник)
The studies of the service life and residual life of various insulating materials are described. The known mathematical models of insulation aging applicable to AC power cable lines are considered. Based on the models and the previously proposed approach, the service life and residual life of cables with XLPE, EPR and PVC insulation are estimated. The assessment is carried out using the data from monitoring the voltage and current of a 6 kV cable transmission line laid at one of the electric power enterprises. Air temperature obtained from open sources. The results showed the applicability of all models for estimating the residual life due to the small difference in the predicted life. In real conditions, the service life of the listed types of insulation can be different due to their dielectric and design features.